2019
DOI: 10.1126/scisignal.aaw2627
|View full text |Cite
|
Sign up to set email alerts
|

The Ca 2+ export pump PMCA clears near-membrane Ca 2+ to facilitate store-operated Ca 2+ entry and NFAT activation

Abstract: Ca2+ signals, which facilitate pluripotent changes in cell fate, reflect the balance between cation entry and export. We found that overexpression of either isoform of the Ca2+-extruding plasma membrane calcium ATPase 4 (PMCA4) pump in Jurkat T cells unexpectedly increased activation of the Ca2+-dependent transcription factor nuclear factor of activated T cells (NFAT). Coexpression of the endoplasmic reticulum–resident Ca2+ sensor stromal interaction molecule 1 (STIM1) with the PMCA4b splice variant further en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…Similarly, another study on mesenchymal-like chemoresistant IGROV1 ovarian cancer cells showed enhanced cell migration as a result of enhanced focal adhesion turnover mediated by SOCE [ 62 ]. It has been suggested that PMCA4b has the ability to decrease near-membrane Ca 2+ concentration in response to SOCE [ 63 ] that may explain, at least partly, the enhanced focal adhesion and reduced motility of the PMCA4b expressing melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another study on mesenchymal-like chemoresistant IGROV1 ovarian cancer cells showed enhanced cell migration as a result of enhanced focal adhesion turnover mediated by SOCE [ 62 ]. It has been suggested that PMCA4b has the ability to decrease near-membrane Ca 2+ concentration in response to SOCE [ 63 ] that may explain, at least partly, the enhanced focal adhesion and reduced motility of the PMCA4b expressing melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Both PMCA1 and PMCA4 are expressed in mouse T cells [8]. Moreover, in human Jurkat T cells, PMCA4 is the leading isoform for calcium clearance and NFAT transcriptional activity [9]. However, mouse B cells can differ from T cells in their requirements for various Ca 2+ handling proteins; for example, the mitochondrial Na + ‐Ca 2+ exchanger NCLX is required for B‐cell migration but not T‐cell migration [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, qPCR analysis of their expression levels failed to support this hypothesis (Fig EV3A); increases in STIM1, Orai3, and PMCA4a were observed in EGR1 −/− , but not EGR4 −/− cells. A modest increase in partner of STIM1 (POST) expression was observed, but this seemed unlikely to account for observed changes in TCR‐mediated Ca 2+ responses reported here. We then considered the possibility that sustained Ca 2+ entry may require compensatory maintenance of membrane potential through potassium channel activity.…”
Section: Resultsmentioning
confidence: 99%